230k views
5 votes
Find the sum of these polynomials (x^6 + x + 9) + (7x^6 + 5) =

User Walter B
by
5.8k points

2 Answers

2 votes

Answer:

8 x^6 + x + 14

Explanation:

Simplify the following:

7 x^6 + x^6 + x + 5 + 9

Grouping like terms, 7 x^6 + x^6 + x + 5 + 9 = (x^6 + 7 x^6) + x + (9 + 5):

(x^6 + 7 x^6) + x + (9 + 5)

x^6 + 7 x^6 = 8 x^6:

8 x^6 + x + (9 + 5)

9 + 5 = 14:

Answer: 8 x^6 + x + 14

User Dean Seo
by
6.0k points
2 votes

For this case we must find the sum of the following polynomials:


x ^ 6 + x + 9\ and\ 7x ^ 6 + 5

We have:


(x ^ 6 + x + 9) + (7x ^ 6 + 5) =

We eliminate parentheses:


x ^ 6 + x + 9 + 7x ^ 6 + 5 =

We add similar terms:


x ^ 6 + 7x ^ 6 + x + 9 + 5 =\\8x ^ 6 + x + 14

Finally we have that the sum of the polynomials is:
8x ^ 6 + x + 14

Answer:


8x ^ 6 + x + 14

User Arbitur
by
5.2k points